2005
DOI: 10.1080/00224490509552275
|View full text |Cite
|
Sign up to set email alerts
|

Differences in psychological health and family dysfunction by sexual victimization type in a clinical sample of African American

Abstract: We examined levels of sexual victimization among a sample of 249 14- to 19-year-old African American adolescent women. Victimization was common: 32.1% reported having been raped, 33.7% had experienced sexual coercion, and 10.8% reported an attempted rape. Only 23.4% had never been victimized. We investigated whether levels of psychological health and family dysfunction varied as a function of the type of sexual victimization. Girls who had been raped had lower levels of self-esteem and mastery and higher level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 115 publications
1
7
0
Order By: Relevance
“…Adaptations to address interpersonal trauma-related cognitions and emotions were informed by the empirical literature and relevant treatment protocols developed for adults exposed to interpersonal trauma (e.g., Cecil & Matson, 2005; Cloitre et al, 2006; DePrince et al, 2010; Resick & Schnicke, 1996). …”
Section: Case Study With Two Adolescentsmentioning
confidence: 99%
“…Adaptations to address interpersonal trauma-related cognitions and emotions were informed by the empirical literature and relevant treatment protocols developed for adults exposed to interpersonal trauma (e.g., Cecil & Matson, 2005; Cloitre et al, 2006; DePrince et al, 2010; Resick & Schnicke, 1996). …”
Section: Case Study With Two Adolescentsmentioning
confidence: 99%
“…A similar trend was observed among women reporting rape by an intimate partner, with 12.2% of African American women affected compared to 9.2% of White women and 8.4% of Hispanic women (Black et al, 2011). Cross-sectional studies conducted among African American women have found higher prevalence estimates, 26.3% for sexual violence and 33.7% for sexual coercion (Cecil & Matson, 2005; Walsh, Koenen, Aiello, Uddin, & Galea, 2014). However, research examining dating violence experienced by African American college students and White college students did not find a significant difference in prevalence by race, indicating that when socioeconomic status is similar between groups, these differences may disappear (Amar, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In a sample of 350 female university students enrolled in psychology courses, Benson et al (2007) found that alcohol consumption was significantly higher among victims of attempted rape or rape, but not significantly higher among victims of sexual coercion or unwanted sexual contact. In a clinical sample of 249 African American female adolescents, Women and Matson (2005) found that the levels of depressive symptoms were significantly higher among rape victims than among those who had not suffered any sexual assault or who were victims of sexual coercion. However, the characteristics of these study samples prevent generalization of their results (i.e., small samples, specific sample types), and thus additional studies are needed to fully examine sexual violence among female university students.…”
Section: Sexual Victimization and Mental Healthmentioning
confidence: 96%